Back to the future: environmental security in nineteenth century global politics. Issue 1 (1st January 2019) - Hough, Peter
ABSTRACT: Environmental security is generally held to be a contemporary or even futuristic concern. However, as with many facets of security thought, this overlooks how the unparalleled technological, economic and social changes of the 19 th Century forged much of the international political landscape we now inhabit. The tendency for ecological political enquiry to focus on the rise of ecocentric policy serves to obscure how many aspects of national and human security relating to environmental change were apparent in the 19 th century. Human insecurity in the face of pollution and resource depletion was a part of the emergence of ecological science in response to the industrialisation of Europe and North America. In addition, this was the era when European imperialism reached its apex and European nationalisms fully emerged; both of which contributed to the national securitization of the environment around much of the world in contrasting ways as the desire to both conquer and preserve nature became more evident. Environmental questions of national, human and ecological security are not peculiar to the present age and were very much apparent in 19 th Century global politics.